1998
DOI: 10.1136/jmg.35.8.637
|View full text |Cite
|
Sign up to set email alerts
|

Studies of FRAXA and FRAXE in women with premature ovarian failure.

Abstract: Recent reports suggest that women with FRAXA premutations have an increased likelihood of having premature ovarian failure (POF). We screened 147 women with idiopathic POF for the number of trinucleotide repeats at the FRAXA and FRAXE loci. We found six women with FRAXA premutations, including four familial and two sporadic cases, but no women with FRAXA full mutations. At the FRAXE locus there were no pre-or full mutations but there was an excess of small alleles with fewer than 11 repeats, including at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 19 publications
4
100
0
5
Order By: Relevance
“…6,7 However the underlying mechanism is not known. One feature of the association is that not all premutation carriers are affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However the underlying mechanism is not known. One feature of the association is that not all premutation carriers are affected.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also studies of women ascertained because of POF have shown that they have about a 2% chance of being a premutation carrier, which can rise to 16% for familial cases. 7 A study by Turner et al 8 suggested an increased incidence of dizygous twinning in premutation carriers but not in full mutations and normal relatives, but this was not substantiated in a study by Sherman et al 9 The rate of dizygous twinning is known to increase with maternal age, 10 and an excess of dizygous twins in premutation carriers might be symptomatic of the generalised premature aging of the ovaries that gives rise to early menopause. Inference might predict that premutation carriers have an excess of trisomic conceptuses, as this too is correlated with advanced maternal age.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies on series of women with POF point in the same direction. In the United Kingdom, the screening of 147 women with idiopathic POF for the fragile X premutation, revealed six premutation carriers (4.1%), four among 25 women with familial POF (16%), and two others among 122 women with sporadic POF (1.6%) (Murray et al, 1998). In Italy, six carriers (6%) were found among 106 FMR1 premutation and premature menopause 425 women with POF, four among 33 familial cases (12%), and two among 73 sporadic cases (3%) (Marozzi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, given that more than 30% of all POF cases are familial, there must be many more POF-causing alleles awaiting discovery. Accordingly, it was a breakthrough when a significant association between the fragile X premutations and POF was demonstrated both by the analysis of women carrying premutations, and by the screening of women affected by POF (Cronister et al, 1991;Schwartz et al, 1994;Conway et al, 1995, Vianna-Morgante et al, 1996Murray et al, 1998;Allingham-Hawkins et al, 1999;ViannaMorgante et al, 1999;Marozzi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Turner Syndrome, ovarian failure is probably due to the haploinsufficiency of genes situated on the critical regions of the X chromosome that escape inactivation (Zinn et al, 1998, Elsheikh et al, 2002, Sybert et al, 2004. In the X Fragile Syndrome, women carrying premutations in FMR1 (Murray et al, 1998, AllinghamHawkins et al, 1999 or presenting microdeletions within the FMR2 gene (Murray et al, 1999) show significant predisposition to develop premature menopause. Furthermore, sequence variants in Xlinked genes have been associated with POF.…”
Section: Introductionmentioning
confidence: 99%